Historical Geography in the Context of the History of Geogaphical Thought and its Relations with the Human Sciences - Vasconcelos, Pedro Almeda (Geografares, 2017)
The text begins with a review of the founding fathers of the academic discipline, with the proposal for the inclusion of I. Kant. It follows with the presentation of “Classical Geographers”; by relations with historians; by Neopositivist Geography and Critical Geography. The question of postmodernity and the end of History and space are discussed as well as the Globalization and the “revenge” of Geography. The text concludes with the relations of Historical Geography with the History of Geographical Thought and with the other Human Sciences.Key-words: Historical Geography; History of Geographical Thought.